1998
DOI: 10.3109/17453679809000935
|View full text |Cite
|
Sign up to set email alerts
|

Attempted unreamed nailing in tibial fractures: A prospective consecutive series of 55 patients

Abstract: We evaluated the possibility of unreamed insertion of an intramedullary nail (IMN) in a consecutive series of 55 tibial shaft fractures in 55 patients (30 men). 43 fractures were closed and 12 fractures were open. All surgeons involved were instructed to try unreamed insertion primarily. Selection of nail diameter was based on measurements of the narrowest part of the medullary canal on preoperative AP- and lateral radiographs, with a millimeter-ruler. Of the 25 cases where a 9 mm nail was chosen, 10 were impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Only 7 studies were prospective [6, 7, 12, 13, 23, 25, 26], while the rest were of retrospective nature [3-5, 8-11, 14-22, 24, 27-30]. Four studies reported on humeral [3, 5, 13, 20], 6 on femoral [6, 9, 14, 21, 28, 29] and 18 on tibial fractures [4, 6-8, 10-12, 14-19, 22-27, 30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 7 studies were prospective [6, 7, 12, 13, 23, 25, 26], while the rest were of retrospective nature [3-5, 8-11, 14-22, 24, 27-30]. Four studies reported on humeral [3, 5, 13, 20], 6 on femoral [6, 9, 14, 21, 28, 29] and 18 on tibial fractures [4, 6-8, 10-12, 14-19, 22-27, 30].…”
Section: Resultsmentioning
confidence: 99%
“…In one study [14], 11 cultures were negative although clinical manifestation of infection occurred. In ten studies [4, 5, 9, 15, 23, 24, 25, 26, 28, 29] the time interval from injury to the primary intramedullary nailing procedure ranged from 3 hours to 33 days.…”
Section: Resultsmentioning
confidence: 99%
“…The inadequate diameter of the tibial canal is not uncommon; the diameter of the canal was <8 mm in 30% of patients in one study. 34 The most important problem for the use of plating in tibial fractures is periosteal damage, 12 which is preventable with less invasive methods. As was mentioned, with the growth in popularity of intramedullary devices, screws and plates have been used less often for a long time, and we did not encounter a recent article about the incidence of infection in patients who received this therapy.…”
Section: Discussionmentioning
confidence: 99%